CD8+ T cells with an intraepithelial phenotype upregulate cytotoxic function upon influenza infection in human lung - Piet, Berber; de Bree, Godelieve J.; Smids-Dierdorp, Barbara S.; van der Loos, Chris M.; Remmerswaal, Ester B.M.; von der Thüsen, Jan H.; van Haarst, Jan M.W.; Eerenberg, Jan P.; ten Brinke, Anja; van der Bij, Wim; Timens, Wim; van Lier, René A.W.; et al. (The Journal of Clinical Investigation, 2011)
The human lung T cell compartment contains many CD8+ T cells specific for respiratory viruses, suggesting that the lung is protected from recurring respiratory infections by a resident T cell pool. The entry site for respiratory viruses is the epithelium, in which a subset of lung CD8+ T cells expressing CD103 (αE integrin) resides. Here, we determined the specificity and function of CD103+CD8+ T cells in protecting human lung against viral infection. Mononuclear cells were isolated from human blood and lung resection samples. Variable numbers of CD103+CD8+ T cells were retrieved from the lung tissue. Interestingly, expression of CD103 was seen only in lung CD8+ T cells specific for influenza but not in those specific for EBV or CMV. CD103+ and influenza-reactive cells preferentially expressed NKG2A, an inhibitor of CD8+ T cell cytotoxic function. In contrast to CD103–CD8+ T cells, most CD103+CD8+ cells did not contain perforin or granzyme B. However, they could quickly upregulate these cytotoxic mediators when exposed to a type I IFN milieu or via contact with their specific antigen. This mechanism may provide a rapid and efficient response to influenza infection, without inducing cytotoxic damage to the delicate epithelial barrier.